1979
DOI: 10.1111/j.1151-2916.1979.tb19114.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Permeability of Sintered Aluminum Oxide

Abstract: Hydrogen permeability of ' gh-density, high-purity sintered alumina tubes was measurh 1s a function of temperature and pressure using tritium as a tracer. The permeability, 4, at 1200" to 1450°C and hydrogen partial pressure between 2 and 50 kPa is:(H atoms cm cm12 s-' kPa-o."J ) = exp(48.95?0.61) exp[ -318.22 18.8 kJ(g.atom)-' (RT)-'] Diffusion coefficients and solubility values deduced from the permeation experiments are consistent with earlier independent measurements. No accelerated permeation due to micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 7 publications
3
26
0
3
Order By: Relevance
“…He found that applying the electric field enhanced the permeation and made the assumption that hydrogen moves as proton. Roberts et al [12] also measured the hydrogen permeability of sintered alumina at high temperature using tritium as a tracer. The permeation rate was reported depending on considerably less than a half power of hydrogen pressure, which suggests that hydrogen migrates as proton under ambipolar diffusion-controlled process.…”
Section: Survey Of Literatures Related To the Proton Conduction In α-mentioning
confidence: 98%
“…He found that applying the electric field enhanced the permeation and made the assumption that hydrogen moves as proton. Roberts et al [12] also measured the hydrogen permeability of sintered alumina at high temperature using tritium as a tracer. The permeation rate was reported depending on considerably less than a half power of hydrogen pressure, which suggests that hydrogen migrates as proton under ambipolar diffusion-controlled process.…”
Section: Survey Of Literatures Related To the Proton Conduction In α-mentioning
confidence: 98%
“…Новые технологии в области металлургии не могут обеспечить полную защиту от проникновения водорода вглубь материала. Поэтому для целей защиты конструкционных и функциональных материалов от водородного охрупчивания остается актуальной разработка технологий создания тонкопленочных покрытий [1][2][3][4][5][6][7][8]. Свойства пленки оксида алюминия (Al 2 O 3 ) были исследованы на сталях и цирконии.…”
Section: Introductionunclassified
“…Свойства пленки оксида алюминия (Al 2 O 3 ) были исследованы на сталях и цирконии. Большинство проведенных исследований на пленках Al 2 O 3 были выполнены в водородной среде при давлениях < 100 kPa и установлено, что окисные пленки (слои) являются эффективным барьером от проникновения водорода [1][2][3][4][5][6][7][8].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Figure 18. Diffusivity of hydrogen in alumina [165,222,243]. The bold line represents the average for many aluminas, reported in Ref.…”
Section: Why Barriers Are Needed For Fusion Reactorsmentioning
confidence: 99%